Social preferences and environmental quality: Evidence from school children in Sierra Leone - Giovanna D'Adda; Ian Levely (Charles University in Prague, Institute of Economic Studies (IES), 2012)
In this paper we examine the effects that variations in the quality of the environment at birth have on children's other-regarding preferences, as measured through four binary-choice dictator games run with school-age children in rural Sierra Leone. We examine the effect of exogenous variations in rainfall level by location and year on children's social preferences. We also study how age at which children had access to improved water sources, such as protected wells, correlates with preferences. Children born within a healthier environment are more generous, when generosity comes at no personal cost, more likely to choose socially efficient allocations and less averse to advantageous inequality. The correlation between rainfall shocks at birth and children's height-for-age suggest that environmental quality affects preferences through its impact on health. We find that proxies for early childhood health affect experimental outcomes in a similar way as age, which helps to explain the process by which individuals develop social preferences. No significant relationship is found in our data between environmental quality and educational outcomes, such as school attendance and grades.
Keywords: C93; I15; D64; 330; Field experiments; Health and Economic Development; Altruism; Inequality Aversion